The Pathophysiology of Fatigue in Parkinson's Disease and its Pragmatic Management. Issue 4 (11th March 2016) - Kostić, Vladimir S.; Tomić, Aleksandra; Ječmenica‐Lukić, Milica
Abstract: Background: Fatigue is 1 of the most common and most disabling symptoms among patients with Parkinson's disease (PD) and has a significant impact on their quality of life. Yet the pathophysiology of fatigue is poorly understood, while its treatment is "limited to an empirical approach based on plausible hypotheses." Methods: PubMed was searched for articles with the key words "Parkinson's disease" or "parkinsonism" and "fatigue" that were published by or before August 2015. The analysis of articles, which were selected on subjective grounds, was used to review the current knowledge of pathophysiology and treatment outcomes in studies focused on fatigue in PD. Conclusions: Clinical and experimental findings support the view that fatigue is a primary manifestation of PD. The main hypothesized pathophysiological mechanisms include abnormal basal ganglia (BG)‐cortical mechanisms, particularly frontal loops, and an imbalance between neurotransmitters (e.g., dopamine [DA] and serotonin), along with an altered hypothalamus‐pituitary‐adrenal axis, neuroinflammation, cardiac sympathetic denervation, etc. Pragmatic treatment of fatigue in patients with PD includes various pharmacological (dopaminergic and psychostimulant drugs, antidepressants) and nonpharmacological strategies, although current knowledge suffers from insufficient evidence to support the use of any drug or nondrug therapy.